Gamma Ray Effect on the Properties of Coumarin C47 Laser Dye (Baghdad Science Journal, 2018)
The research is concerned about studying the absorption spectrum of the solution coumarin dye C47. The chloroform solvent was used with C47 dye in three different concentrations 10-4, 10-5 and 10-6 M. The laser dye solution was prepared by dissolving the required amount of dye in chloroform alcohol, while studying absorption spectrum before and after irradiation with gamma ray by cobalt-60 source 60Co at exposure time, which are 0, 4, 6 and 18 hours with different absorbed doses 0, 136, 204 and 612 Gy.The results show that red shift in the absorption spectrum was increased by increasing the concentration of laser dye solutions , while the increase of gamma dose led to increase the red shift after irradiation, as the exposure period and irradiation dose increased from gamma ray at 60Co source. Furthermore, the decrease in the concentrations of laser dye solutions shifts the absorption spectrum peak towards the short wavelength blue shift.